Quality of 'Fuji Suprema' apples subject to different mechanical damages Qualidade de Maçãs 'Fuji Suprema' Submetidas A Diferentes Tipos de Dano Mecânico - Hendges M.V.* (2011)
The objective of this work was to evaluate the effect of mechanical damage by impact, compression and cut on the quality of 'Fuji Suprema' apples in ambient conditions. The treatments were: control (no mechanical damage) and mechanical damage by impact, compression and cut. Different mechanical damages did not influence the flesh firmness and hue angle of the skin. Cut damage provided fruits with lower titratable acidity, nine days after damages application. Fruits submitted to damage by impact showed higher soluble solids content, 15 days after damages application. For the L color index of the flesh, cut and impact damages caused the smallest value in all evaluations, characterizing the flesh browning. However, this effect was not observed in the skin. Cut damage presented 100% of decay incidence to the nine days after mechanical damages application. In general, it can be conclude that 'Fuji Suprema' apples submitted to damage by impact and cut showed loss quality, because they haveflesh browning incidence in the damage place. Moreover, cut damage reduces postharvest life of fruits, facilitating higher percentage of rots.